Spatial scales matter in designing buffer zones for coastal protected areas along the East Asian-Australasian Flyway - Roger H. Lee; Ivan H.Y. Kwong; Tom C.H. Li; Paulina P.Y. Wong; Yik-Hei Sung; Yat-Tung Yu (Global Ecology and Conservation)
Coastal protected areas are increasingly threatened by urbanization, posing significant risks to wetland biodiversity. Consequently, the recognition of buffer zones as essential for reducing anthropogenic impacts on protected areas has grown. However, limited monitoring and research efforts have been directed towards areas beyond protected sites, despite their interconnectedness. In this study, we focused on waterbirds as ecologically important wetland species to provide evidence of the significance of monitoring and managing buffer zones. By integrating remotely sensed parameters and 3-year monthly waterbird surveys in and around the Mai Po Inner Deep Bay Ramsar Site of Hong Kong, a key stopover of the East Asian Australasian Flyway, we mapped waterbird occurrences for all and different waterbird guilds during winter and summer using random forest models. We found that suitable habitats were predominantly found within protected areas, yet ardeids, large wading birds, ducks and grebes also relied on buffer zones. Waterbird occurrences were influenced by the spatial extent of suitable habitats, with variations observed across different guilds and seasons. In the study area, maintaining at least 40 % open water within an 800-meter radius of key habitats better supports diverse waterbird guilds and should inform the design of waterbird-friendly landscape profiles for protected areas and their buffer zones. Our findings reinforce the significant contribution of protected coastal wetlands to waterbird conservation and highlight the growing importance of spatially relevant buffer zones in facilitating a gradual transition between protected and urbanized areas in supporting waterbird diversity amidst coastal developments.